Réponses

2013-04-23T19:19:21+02:00

3x+7=x+2

2x=-5

x=-5/2

 

4a-7=-2a+1

6a=8

a=8/6

 

3x+4=-2x+4

5x=0

x=0

 

3x-5=-4x+3

7x=5

x=5/7

  • Utilisateur Brainly
2013-04-23T19:23:07+02:00

 a)

3x+7=x+2

3x+7-x=x+2-x

2x+7=+2

2x+7-7=+2-7

2x=-5

x=-5/2

x=-2.5

 

b)

4a - 7=-2a + 1

4a-7+2a=-2a+1+2a

6a-7=+1

6a-7+7=+1+7

6a=8

a=8/6

 

 

 

c)

3x+4=-2x +4

3x+4+2x=-2x+4+2x

2x+4=+4

2x+4-4=4-4

2x=0

x=0/2

x=0

 

 

d)

3x - 5= 4x + 3

3x-5-4x=4x+3-4x

-1x-5=+3

-1x-5+5=+3+5

-1x=8

x=8/-1

x=-8

 

voilà....... :)